Panel data in research on mobility and migration: A review of recent advances - Sergi Vidal; Philipp M. Lersch (Comparative Population Studies (CPoS), 2021)
Panel data has become the gold standard for causal assessments of complex human behaviour in quantitative social science. The objective of this review is to examine and discuss how panel data and related methods contribute to the identification of causal relationships in spatial mobility research. We illustrate this by providing a succinct overview of recent progress in spatial mobility research, drawing on panel data. The review outlines research from a number of scholarly disciplines that maps patterns, establishes determinants and assesses the impact of spatial mobility for a range of outcomes. Studies presented in this article are used to decipher complex interdependencies over the life course, scrutinise the selectivity of migrants, and shed light on the interplay between individual agency, social embeddedness and socio-structural contexts. The article concludes with a set of critical issues for future research.
urn:nbn:de:bib-cpos-2021-07en3
Keywords: 300; Internal migration; Life course; Longitudinal methods; Panel data; Residential mobility